2017
DOI: 10.3390/nu9090959
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-Rich Extract of Paulownia fortunei Flowers Attenuates Diet-Induced Hyperlipidemia, Hepatic Steatosis and Insulin Resistance in Obesity Mice by AMPK Pathway

Abstract: The flavonoid-rich extract from Paulownia fortunei flowers (EPF) has been reported to prevent obesity and other lipid metabolism disease. However, the mechanism of its protective effects is not yet clear. The objective of this study was to investigate molecular factors involved in the hypoglycemic and hypolipidemic effects of EPF in obese mice fed a high-fat diet (HFD). Male h ICR (Institute of Cancer Research) mice were fed a HFD containing or not containing the EPF (50 or 100 mg/kg) for eight weeks. EPF redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…This Special Issue “Effects of Polyphenol-Rich Foods on Human Health” comprises 64 peer-reviewed papers, including 43 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], one case-report [ 51 ] and 20 literature reviews [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ...…”
mentioning
confidence: 99%
“…A large number of studies have reported the beneficial effects of dietary flavonoids on human health (Hossain et al, 2016). Numerous flavonoids including those in Paulownia fortunei flowers, green tea, and cinnamon have been found to protect against obesity-related complications, such as type 2 diabetes mellitus, cardiovascular disease, and nonalcoholic fatty liver disease (Liu et al, 2017;Tuzcu, Orhan, Sahin, Juturu, & Sahin, 2017;Yamashita et al, 2018). However, to our knowledge, there is no report on anti-obesity activity of prenylated flavonoids in the seeds of P. corylifolia L. We found that PFE protected against obesity and significantly reduced bodyweight, fat mass, and white adipose cells in the HFD-induced obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the protein expression of HMGCR which is the target gene of miR-93-3p was similar in control and GDM mice, while protein expression of miR-188-5p target gene CPT1A was significantly reduced in GDM mice and it can be notably reversed by LBP treatment. CPT1A can catalyze the entrance of fatty acids into the mitochondria and it is the rate limiting enzyme of hepatic fatty acid β-oxidation [33].…”
Section: Discussionmentioning
confidence: 99%